Reconstrucción del sistema de tiempo, aspecto y modo del protocriollo inglés del Atlántico - Portilla, Mario (2015)
This study presents a diachronic reconstruction of the time, aspect and mood system (TAM) corresponding to the Atlantic proto-creole. One time category (expressed by two markers), four aspect categories (progressive, durative, habitual, and completive), one mood category (expressed by two markers), and four modal verbs are reconstructed.